2018
DOI: 10.1038/s41598-018-21641-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular subtypes of Alzheimer’s disease

Abstract: Protein misfolding and aggregation is a central feature of several neurodegenerative disorders including Alzheimer’s disease (AD), in which assemblies of amyloid β (Aβ) peptides accumulate in the brain in the form of parenchymal and/or vascular amyloid. A widely accepted concept is that AD is characterized by distinct clinical and neuropathological phenotypes. Recent studies revealed that Aβ assemblies might have structural differences among AD brains and that such pleomorphic assemblies can correlate with dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 61 publications
2
44
0
1
Order By: Relevance
“…Both Aβ aggregates purified from brains and Aβ aggregates formed from synthetic peptides can initiate Aβ deposition when inoculated into transgenic mice, and Aβ-injected animals exhibit electrophysiology and neurogenesis deficits as well as neuronal death [ 61 , 73 ]. Moreover, like prions, Aβ aggregates can exist as distinct strains with unique conformational properties that produce different pathological phenotypes upon injection into mice [ 13 , 15 , 28 , 47 , 60 , 68 ]. It has also been suggested that a prion-like transmission mechanism may explain the presence of cerebral Aβ pathology in individuals that have received human growth hormone treatments, dura mater grafts, or have undergone neurosurgery [ 10 , 16 , 20 , 23 , 30 , 32 , 33 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both Aβ aggregates purified from brains and Aβ aggregates formed from synthetic peptides can initiate Aβ deposition when inoculated into transgenic mice, and Aβ-injected animals exhibit electrophysiology and neurogenesis deficits as well as neuronal death [ 61 , 73 ]. Moreover, like prions, Aβ aggregates can exist as distinct strains with unique conformational properties that produce different pathological phenotypes upon injection into mice [ 13 , 15 , 28 , 47 , 60 , 68 ]. It has also been suggested that a prion-like transmission mechanism may explain the presence of cerebral Aβ pathology in individuals that have received human growth hormone treatments, dura mater grafts, or have undergone neurosurgery [ 10 , 16 , 20 , 23 , 30 , 32 , 33 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Αβ deposits in the brain can differ significantly between different conditions, such as pathological ageing [34] and AD [35]. Molecular subtypes of AD have also been reported, based on the relative abundance of observed Αβ peptides, each of which show different aggregation kinetics and resistance to degradation [36]. Hitherto, Αβ42 is one of the most well characterized diagnostic biomarkers for AD and it is well established that the concentration of Αβ42 is decreased in cerebrospinal fluid (CSF) from AD patients compared to healthy controls [37].…”
mentioning
confidence: 99%
“…Over the last decade, some insights into the understanding of AD have come from studies of the prion diseases in which cell-to-cell transmission is achieved by templated misfolding of the normal protein substrate by the conformationally variant prion. AD is believed to exist in a number of subtypes, with experimental data indicating that different conformations of Ab and tau misfolded protein might underlie distinct pathologic phenotypes, a phenomenon possibly analogous to the multiple strains of the prion diseases (5)(6)(7)(8). In addition, the misfolded proteins in AD act as seeds for "prion-like" conversion of normally folded protein to abnormal conformations (9,10).…”
mentioning
confidence: 99%